STRATEGIC INITIATIVES OF THE UNITED STATES AND CHINA IN CENTRAL ASIA - Akram A. Umarov (Сравнительная политика, 2015)
The article presents a comparative analysis of the U.S. strategy “New Silk Road” and the project of China to establish economic belt “Silk Road”, as well as their implementation in Central Asia. However, the unstable situation in Afghanistan, the lack of sources of financing capital-intensive infrastructure projects, the existence of various contradictions between the countries of this region and other reasons prevent the full implementation of the U.S. strategy. At the same time, the Chinese project faces a lack of precision uncertainty of funding.